Augmented Reality in Learning the Introduction to the Toba-Simalungun Batak Language Using the Marker-Based Tracking Method - Simbolon, Andreas; Nasution, M Irfan Aldy (Marqcha Institute, 2025)
Regional languages ​​are invaluable cultural treasures and are inseparable from socio-cultural values ​​that reflect the principles of regional behavior and identity. In the areas where tribes are spread in North Sumatra Province, there are several languages ​​such as Batak Toba and Simalungun which are used in several areas in North Sumatra. Global developments have made the use of Batak Toba and Simalungun languages ​​​​decrease and the intention to learn from children to adults is decreasing and the lack of learning facilities to understand Batak Toba and Simalungun languages. This study will aim to combine Batak Toba and Simalungun languages ​​​​with augmented reality (AR) technology in order to obtain more efficient, interesting and interactive learning facilities for children to adults in learning Batak Toba and Simalungun languages. The application development method uses Marker Based Tracking as an augmented reality (AR) reference in the development of the Android-based Batak Toba-Simalungun Language Introduction Learning Application Marker Based Tracking Method. The Marker-Based Tracking method for the Toba-Simalungun Batak language, produced in this application, is a 3-dimensional (3D) image of the language. When the user points the camera at an object or 3D image, the application displays a 3-dimensional (3D) image of the Toba-Simalungun Batak language pattern captured by the user's camera.